First we need to put this question in the form of an equation.

Let's suppose the number is 'x'.

Twice of the number would be 2x. Its sum with three can be shown as:

2x+3

Four times this value equals 12, so:

4(2x+3)=12

Now, you can solve for x. The answer you get would be the number:

4(2x+3)=12

8x+12=12

8x=12-12

8x=0

x=0/8

x=0

So, the number in the question is 0.

To verify, put it in the equation we made:

4(2x+3)=12

4[2(0)+3)]=12

4(0+3)=12

4(3)=12

12=12

Since both sides are equal, our answer is correct.

Let's suppose the number is 'x'.

Twice of the number would be 2x. Its sum with three can be shown as:

2x+3

Four times this value equals 12, so:

4(2x+3)=12

Now, you can solve for x. The answer you get would be the number:

4(2x+3)=12

8x+12=12

8x=12-12

8x=0

x=0/8

x=0

So, the number in the question is 0.

To verify, put it in the equation we made:

4(2x+3)=12

4[2(0)+3)]=12

4(0+3)=12

4(3)=12

12=12

Since both sides are equal, our answer is correct.